2001
DOI: 10.1590/s0101-20612001000100006
|View full text |Cite
|
Sign up to set email alerts
|

Estudo da adição de vital glúten à farinha de arroz, farinha de aveia e amido de trigo na qualidade de pães

Abstract: RESUMOFarinhas de arroz e de aveia e amido de trigo foram adicionados de vital glúten e avaliados pelo Teste de Panificação. Usou-se como padrão uma amostra de farinha de trigo com característi-cas adequadas para produção de pão. Os níveis de adição de vital glúten foram de 10, 15, 17,5, 20 e 30% para a farinha de arroz e de 10, 20 e 30% para a farinha de aveia. Ao amido de trigo, extraído da farinha de trigo utilizada como padrão, foi adicionado vital glúten de forma a reconstituir o teor de glúten original d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 2 publications
1
5
0
10
Order By: Relevance
“…The results of protein, lipids, fiber, and ash obtained for the broken rice flour are close to those reported by Mendonça, Ascheri and Ascheri (2001), Tedrus et al (2001), Dors, Castiglioni and Ruiz (2006) and consistent with the Brazilian Table of Food Composition (UNIVERSIDADE…, 2006), which shows protein contents varying from 6.83% to 9.81%; fibers from 0.17% to 1.70%; lipids from 0.30% to 0.89%, fibers from 0.17% to 1.70% and ash from 0.2% to 0.78%. The moisture content of the broken rice set at 11.74 % is close to the values in the Brazilian The results also show that the extrusion and drying processes led to loss of moisture, which was predictable since , of recuperated amino acids in a study with 13 brands of flaked cereals.…”
Section: Technological Characterization Of the Breakfast Flakesupporting
confidence: 91%
“…The results of protein, lipids, fiber, and ash obtained for the broken rice flour are close to those reported by Mendonça, Ascheri and Ascheri (2001), Tedrus et al (2001), Dors, Castiglioni and Ruiz (2006) and consistent with the Brazilian Table of Food Composition (UNIVERSIDADE…, 2006), which shows protein contents varying from 6.83% to 9.81%; fibers from 0.17% to 1.70%; lipids from 0.30% to 0.89%, fibers from 0.17% to 1.70% and ash from 0.2% to 0.78%. The moisture content of the broken rice set at 11.74 % is close to the values in the Brazilian The results also show that the extrusion and drying processes led to loss of moisture, which was predictable since , of recuperated amino acids in a study with 13 brands of flaked cereals.…”
Section: Technological Characterization Of the Breakfast Flakesupporting
confidence: 91%
“…This probably is the reason of specific volume decreasing and density increasing in 15% BBEF and CEF breads. Literature data demonstrate that extruded cowpea and black bean flour present minor water solubility and high water absorption than wheat flour (Tedrus and others 2001; Batista and others 2010a, 2010b), which affect dough properties.…”
Section: Resultsmentioning
confidence: 99%
“…According to Tedrus et al [31], wheat flour is the only one able to produce a viscoelastic mass with better gas holding during brew and first steps of baking, getting a softer food. According to a study that had used wheat flour replacements in cookies, the results showed that instrumental attributes did not alter between traditional and quinoa flour samples.…”
Section: Instrumental Analysis and Correlationmentioning
confidence: 99%